2022
DOI: 10.3389/fonc.2022.949715
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR Screening Reveals Pyrimidine Metabolic Reprogramming in 5-FU Chronochemotherapy of Colorectal Cancer

Abstract: ObjectiveDisruption of the circadian rhythm is associated with cancer occurrence, response to chemotherapy, and poor prognosis. Thus, using internal clock-based chronotherapy to optimize the administration time may improve the therapeutic effects of anticancer drugs while reducing the side effects. Chronotherapy with 5-fluorouracil (5-FU) has been observed in colorectal cancer (CRC) for a long time, but its effect is under controversial and the mechanism remains unclear.MethodsGenome-wide clustered regularly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These findings demonstrated that GBH blocked purine and pyrimidine synthesis and further impaired genetic information in testicular cells. In addition, Ak5, Guk1, Nme2, Entpd2, and Upp2 are key genes involved in the nucleotide synthesis and metabolism, which directly or indirectly regulate DNA and RNA synthesis 45–49 . In this study, the expression of Ak5, Guk1, and Nme2 significantly decreased, but Entpd2 and Upp2 increased in purine and pyrimidine metabolism pathways.…”
Section: Discussionmentioning
confidence: 53%
“…These findings demonstrated that GBH blocked purine and pyrimidine synthesis and further impaired genetic information in testicular cells. In addition, Ak5, Guk1, Nme2, Entpd2, and Upp2 are key genes involved in the nucleotide synthesis and metabolism, which directly or indirectly regulate DNA and RNA synthesis 45–49 . In this study, the expression of Ak5, Guk1, and Nme2 significantly decreased, but Entpd2 and Upp2 increased in purine and pyrimidine metabolism pathways.…”
Section: Discussionmentioning
confidence: 53%
“…It has been shown that when 5-Fu exerts its antitumor mechanism of action, UMPS can convert a part of 5-Fu into components with cytotoxicity, thus inhibiting the activity of the proapoptotic protein, Bok. This allows cancer cells in a nonproliferative state to escape the damaging properties of 5-Fu and develop secondary drug resistance [ 32 35 ]. Yu et al also verified the modulation of 5-Fu drug sensitivity by UMPS expression through their findings [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…UMPS is an enzyme that metabolizes 5-FU into other metabolites with cytotoxic activity and is considered to be a major regulator of the cytotoxic effects of 5-FU [ 53 ]. One study included in this review reported an association of the UMPS rs4678145 and rs2279199 SNPs with asthenia and severe nausea/vomiting in CRC patients treated with capecitabine-based regimens [ 25 ].…”
Section: Discussionmentioning
confidence: 99%